Blockchain for maritime supply chain: Efficiency and security advancements - Curado, J.; Bhandari, M.; Ferreira, J. C.; Martins, A. L. (IEEE Access, 2025)
The maritime supply chain plays a vital role in global trade, but it continues to face major challenges, including transparency issues, fraud, and data privacy concerns. Blockchain technology has emerged as a promising solution to make the supply chain more secure, efficient, and trustworthy across the system. However, it still encounters limitations, especially regarding privacy and the handling of large volumes of data. To address these issues, Zero-Knowledge Proofs (ZKPs) offer a viable solution, enabling the validation of documents and transactions without revealing sensitive information. This helps maintain confidentiality while meeting regulatory requirements, such as those set by the eFTI regulation. This paper investigates blockchain adoption in maritime supply chains with a focus on ZKP integration for secure document verification, fraud mitigation, and regulatory compliance. It evaluates computational overhead, scalability, and adoption barriers, and proposes a framework supported by simulation-based validation using Ethereum and ZoKrates to assess feasibility and performance. By combining ZKPs with blockchain, this approach enhances a secure, transparent, and efficient trade ecosystem, optimising resources and reducing risks. Future research directions are outlined to advance sustainable maritime logistics.